2008
DOI: 10.1038/jp.2008.62
|View full text |Cite
|
Sign up to set email alerts
|

Gestational diabetes: diagnosis and management

Abstract: Purpose: To review the diagnosis and management of gestational diabetes.Epidemiology: In the United States, approximately 2 to 5% of all pregnant women have gestational diabetes. Those women with a family history of type 2 diabetes mellitus, Asian or native American race, Latina ethnicity or obesity are at higher risk for developing gestational diabetes. Conclusion:Women with gestational diabetes who are treated appropriately can achieve good outcomes in the majority of pregnancies. Frequent blood glucose moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 72 publications
3
28
0
6
Order By: Relevance
“…W największym stopniu ryzyko urodzenia dziecka z wadą dotyczy kobiet, które zachorowały na cukrzycę przed ciążą. W cukrzycy ciążowej ryzyko to jest niewielkie [18]. Wadą płodu najbardziej charakterystyczną dla cukrzycy, aczkolwiek bardzo rzadko występującą, jest zespół zanikowy okolicy krzyżowej (caudal regression syndrom), polegający na sekwencji zmian malformacyjnych obejmujących atrezję odbytu, agenezję kręgosłupa krzyżowego, lędźwiowego i dolnej czę-ści piersiowego.…”
Section: Wady Wrodzoneunclassified
See 3 more Smart Citations
“…W największym stopniu ryzyko urodzenia dziecka z wadą dotyczy kobiet, które zachorowały na cukrzycę przed ciążą. W cukrzycy ciążowej ryzyko to jest niewielkie [18]. Wadą płodu najbardziej charakterystyczną dla cukrzycy, aczkolwiek bardzo rzadko występującą, jest zespół zanikowy okolicy krzyżowej (caudal regression syndrom), polegający na sekwencji zmian malformacyjnych obejmujących atrezję odbytu, agenezję kręgosłupa krzyżowego, lędźwiowego i dolnej czę-ści piersiowego.…”
Section: Wady Wrodzoneunclassified
“…Poważnym powikłaniem takiego porodu może być niedotlenienie lub/i uszkodzenie splotu barkowego. Ryzyko wystąpienia tych powikłań u noworodka z makrosomią spowodowaną cukrzycą matczyną jest większe niż u dziecka o tej samej masie ciała, którego matka jest zdrowa [18]. Poza charakterystycznym wyglądem: cushingoidalna budowa ciała, żywo czerwona skóra, obfite owłosienie obejmujące również małżowiny uszne, u noworodków z fetopatią cukrzycową obserwuje się liczne nieprawidłowości przebiegu okresu okołoporodowego, takie jak: hipoglikemia, zaburzenia oddychania, elektrolitowe, hematologiczne, neurologiczne, kardiologiczne.…”
Section: Makrosomiaunclassified
See 2 more Smart Citations
“…7 Evidence suggests that proper disease management can lead to improved perinatal outcomes. 2,[8][9][10][11] The potential for excessive fetal growth outcomes coupled with the complexity of medical management among women with GDM suggests that prenatal care may be associated with improved outcomes. The research reported here examines the degree to which excessive fetal growth outcomes vary across levels of prenatal care among women with GDM.…”
Section: Introductionmentioning
confidence: 99%